SAT0368 How Patients Self-Manage Rheumatoid Arthritis Flares: Findings from Catch. (9th June 2015) - Bartlett, S.J.; Bingham, C.O.; Lin, D.; Boire, G.; Hitchon, C.A.; Haraoui, B.; Keystone, E.; Tin, D.; Thorne, J.C.; Pope, J.; Bykerk, V.P.
Abstract : Background: More than 25% of early rheumatoid arthritis (ERA) patients attending routine clinic visits report experiencing significant increases in disease activity (flares). In focus groups, patients described using a range of self-management strategies (SMS) to manage flares. Here, we describe SMS reported by patients in large Canadian observational study of ERA (CATCH). Methods: 388 of 501 participants with ERA reported being in a flare. Flaring patients were mostly female (77%), white (80%) and educated (56% > High School). At each visit, patients who reported being in a flare provided ratings of its severity (10 point VAS), duration and additional SMS used to manage the flare. SMS queried were selected from a list previously identified in focus groups with RA patients in 5 countries as part of the ongoing efforts of the OMERACT RA Flare Group. Results: The most common SMS included using analgesics and reducing activities (53% and 52%, respectively) and behavioural approaches (i.e., massage, warm/cold packs, exercise) and avoiding activities (36% and 35% respectively); 6% used steroids and 17% called their physician for help. Use of SMS increased with flare duration; whereas 30% reported using no additional SMS in the first week, >7 days, only 15% reported using no additional SMS (p<.05). A similar pattern was seen with flare severity: 40% of patients didn't do anything differently with flares <4 vs. 15% of those who rated severity ≥4 (p<.05). Higher flare severity was associated with significantly greater activity reduction (60% vs. 28%) and avoidance (42% vs. 15%) and use of analgesics (58% vs. 34%)(p's <.05). Men, more than women, reported not doing anything differently in response to their flare (31% vs. 17%; p<.05); 40% of women reported using non-pharmacological approaches to manage their flare vs. 22% of men, whereas rates of reducing/avoiding activities and using painkillers or steroids were similar (p>.05) between sexes. Those more recently diagnosed (0-12 months) were significantly more likely to add additional SMS compared to those with established disease (>12 months: 85% vs. 75%) by using painkillers (61% vs. 47%), avoiding activities (43% vs. 27%) and calling their doctor (25% vs. 11%)(p's <.05). As compared to those who did not call their doctor for help, patients who called were significantly more likely (p<.05) to avoid activities (51% vs. 32%), and use analgesics (49% vs. 69%) and steroids (3% vs. 21%). Among those with flare severity ≥4 and duration >7d, 88% used additional SMS including reducing activities (63%), using analgesics (61%), avoiding activities (45%), non-pharmacological approaches (40%) or calling their doctor (22%). Conclusions: Use of self-management strategies accompany reports of flare in RA and are more frequent with higher flare severity (≥4) and duration (>1 week). Strategies include limiting participation/role activities and using additional medications and behaviors aimed to reduce symptoms. SMS highlight the impact of RA flares on quality of life with implications regarding added costs. Disclosure of Interest: S. Bartlett: None declared, C. Bingham: None declared, D. Lin: None declared, G. Boire: None declared, C. Hitchon: None declared, B. Haraoui: None declared, E. Keystone: None declared, D. Tin: None declared, J. C. Thorne: None declared, J. Pope: None declared, V. Bykerk Grant/research support from: The CATCH study was designed and implemented by the investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant since the inception of CATCH. As of 2011, further support was provided by Hoffmann-LaRoche Ltd., UCB Canada Inc., Bristol-Myers Squibb Canada Co., AbbVie Corporation (formerly Abbott Laboratories Ltd.), and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson & Johnson Inc.)